Efficient Enzyme-Assisted Extraction and Conversion of Polydatin to Resveratrol From Polygonum cuspidatum Using Thermostable Cellulase and Immobilized β-Glucosidase - Wang, Chunqing; Liu, Xiaolong; Zhang, Mengle; Shao, Haoyue; Zhang, Manman; Wang, Xiaomeng; Wang, Qinghua; Bao, Zhining; Fan, Xinjiong; Li, He (Frontiers in Microbiology, 2019)
Resveratrol, a bioactive compound in high quantities in Polygonum cuspidatum, has well-known health benefits. However, it mainly exists in its glycosidic form, polydatin, in plants. To increase the production of resveratrol for various uses in medicine, foods, and cosmetics, an efficient deglycosylation technique is needed for converting polydatin into resveratrol. We screened a new cellulolytic strain of Bacillus from herb compost, and we optimized parameters within the fermentation process using response surface methodology with a Box-Behnken design. The yield of cellulase reached 2701.08 U/L, corresponding to values that were 5.4 times as high as those under unoptimized conditions. The Bacillus cellulase possessed good thermostablity and was stable under both acidic and neutral conditions. The cellulase was then used in the pretreatment of P. cuspidatum root. After incubation at 50 °С for 4 hours with shaking at 150 rpm, the contents of piceid and resveratrol were determined to be 7.60 ± 0.15 and 9.72 ± 0.29 mg/g, respectively. To obtain complete deglycosylation, immobilized β-glucosidase (bgl2238) was added to the cellulase-treated extracts of P. cuspidatum root to convert residual polydatin into resveratrol. After the first cycle, the contents of piceid and resveratrol were determined to be 0 and 13.69 ± 0.30 mg/g, respectively. Moreover, enzyme activity showed little loss during up to 4 consecutive cycles. These results demonstrated that the immobilized β-glucosidase possessed high deglycosylation activity and outstanding operational stability. The mixture of Bacillus cellulase and immobilized bgl2238 appears promising as a means to increase the supply of resveratrol in the medicine market worldwide.